Semi‐continuous scale‐down models for clone and operating parameter screening in perfusion bioreactors. (13th March 2019) - Bielser, Jean‐Marc; Domaradzki, Jakub; Souquet, Jonathan; Broly, Hervé; Morbidelli, Massimo
Abstract : Perfusion cell culture, confined traditionally to the production of fragile molecules, is currently gaining broader attention in the biomanufacturing of therapeutic proteins. The development of these processes is made difficult by the limited availability of appropriate scale‐down models. This is due to the continuous operation that requires complex control and cell retention capacity. For example, the determination of an optimal perfusion and bleed rate for continuous cell culture is often performed in scale‐down bioreactors and requires a substantial amount of time and effort. To increase the experimental throughput and decrease the required workload, a semi‐continuous procedure, referred to as the VCDmax (viable cell density) approach, has been developed on the basis of shake tubes (ST) and deepwell plates (96‐DWP). Its effectiveness has been demonstrated for 12 different CHO‐K1‐SV cell lines expressing an IgG1. Further, its reliability has been investigated through proper comparisons with perfusion runs in lab‐scale bioreactors. It was found that the volumetric productivity and the CSPRmin (cell specific perfusion rate) determined using the ST and 96‐DWP models were successfully (mostly within the experimental error) confirmed in lab‐scale bioreactors, which then covered a significant scale‐up from the half milliliter to the liter scale. These scale‐down models are very useful to design and scale‐up optimal bioreactor operating conditions as well as screening for different media and cell lines.